Dose-dependent QTc interval prolongation under haloperidol and pipamperone in the management of delirium in a naturalistic setting - Philipp Bohny; Philipp Bohny; Soenke Boettger; Josef Jenewein; Josef Jenewein (Frontiers in Psychiatry, 2023)
ObjectiveDelirium is an acute, life-threatening neuropsychiatric disorder frequently occurring among hospitalized patients. Antipsychotic medications are often recommended for delirium management but are associated with cardiovascular risks. This study aimed to investigate the frequency and magnitude of QTc interval prolongation and clinically relevant side effects occurring in delirium patients managed with haloperidol and/or pipamperone.MethodsThis descriptive retrospective cohort study evaluated 102 elderly (mean age: 73.2 years) inpatients with delirium treated with either haloperidol, pipamperone, a combination of both, or neither in a naturalistic setting over the course of up to 20 days or until the end of delirium.ResultsA total of 86.3% of patients were treated with haloperidol and/or pipamperone at a mean daily haloperidol-equipotent dose of 1.2 ± 1 mg. Non-cardiovascular side effects were registered in 2.9% of all patients and correlated with higher scores on the Delirium Observation Screening Scale. They did not occur more frequently under antipsychotic treatment. The frequency of QTc interval prolongation was comparably common among all groups, but prolongation magnitude was higher under antipsychotic treatment. It was positively correlated with antipsychotic dosage and the total number of QTc interval-prolonging substances administered. Critical QTc interval prolongation was registered in 21.6% (n = 19) of patients in the group treated with antipsychotics compared to 14.3% (n = 2) of patients in the unmedicated group; however, the difference was not statistically significant. Polypharmacy was associated with a higher risk of critical QTc interval prolongation and increased mortality during delirium.ConclusionDelirium treatment with haloperidol and/or pipamperone was not associated with a higher risk of QTc-interval prolongation in this naturalistic patient sample but was greater in magnitude and correlated with equipotent dosage and the number of QT interval-prolonging substances used. Polypharmacy was associated with higher mortality and increased risk of critical QTc prolongation.